The New Geography of Labor Markets - Mert Akan; José María Barrero; Nicholas Bloom; Tom Bowen; Shelby Rae Buckman; Steven J. Davis; Hyoseul Kim (Institute of Labor Economics (IZA), 2025)
We study where Americans live in relation to their employer's worksite using matched employer-employee data, and how that relationship changes with the rise of work from home (WFH). Mean distance from home to employer's worksite rose more than 70% between 2019 and 2024 in our dataset. Twelve percent of employees hired after March 2020 reside fifty or more miles from their employer by 2024, triple the pre-pandemic share. Distance to employer rose most for those in their 30s and 40s, among highly paid employees, and in Finance, Information, and Professional Services. Especially for the affluent, the pandemic-instigated rise in WFH initiated a multi-year pattern of net migration to areas with cheaper housing and states with lower tax rates. Finally, we show that distant employees exhibit more sensitivity to firm-level adjustments on hiring and separation margins. These developments have implications for residential location, state-level tax revenues, labor markets, and household welfare.
Keywords: J2; J3; R1; 330; work from home; remote jobs; distance to employer; hires and separations; taxes and relocation; housing costs and relocation; worker migration; geographic extent of labor markets